STRATEGIES FOR INDIAN MANUFACTURING FIMRS A FOCUS ON BRANDING & COUNTRY OF ORIGIN EFFECTS ON CONSTRUCTION EQUIPMENTS - Mehta, Aditya Vikram (2006)
Various research studies have been conducted to analyse the importance and competitive advantages of consumer brands and the effects of their country of origin. However little research has gone into branding and country image effects which apply on business-to-business products. We then look into the aspects of challenges faced by growing manufacturing industries in India, which are facing fierce competition from international manufacturers. We try to explore if the possible reasons for such high competitive advantages enjoyed by European manufacturers. Taking brand identity and country of origin as our cues for research, we identify its values in the b2b industries.